2001
DOI: 10.1007/s10024001-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

RET Men2B -transgene Produces Sympathoadrenal Tumors But Does Not Prevent Intestinal Aganglionosis in gdnf −/− or gfrα-1 −/− Mice

Abstract: Multiple endocrine neoplasia type 2B (MEN2B) syndrome is caused by a missense mutation in the RET gene, which replaces Met918 by Thr in the intracellular kinase domain of the protein. This single amino acid substitution transforms the receptor into a constitutively active monomeric kinase (RET(Men2B)) and produces an autosomal dominant syndrome characterized by medullary thyroid carcinoma, pheochromocytomas, musculoskeletal anomalies, and mucosal ganglioneuromas. The ligand, GDNF, stimulates RET activity throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Approximately one half of the familial and one fifth of the sporadic mutations of Hirschsprung disease are associated with RET. Hirschsprung disease has been associated with multiple endocrine neoplasia types 2A and 2B, familial medullary thyroid carcinoma, and the Waardenburg‐Shah syndrome (hypopigmentation and cochlear neurosensory deafness) (23‐25). Currently, the only therapy available for affected individuals is resection of the aganglionic intestine.…”
Section: Introduction and General Concepts On The Enteric Nervous Systemmentioning
confidence: 99%
“…Approximately one half of the familial and one fifth of the sporadic mutations of Hirschsprung disease are associated with RET. Hirschsprung disease has been associated with multiple endocrine neoplasia types 2A and 2B, familial medullary thyroid carcinoma, and the Waardenburg‐Shah syndrome (hypopigmentation and cochlear neurosensory deafness) (23‐25). Currently, the only therapy available for affected individuals is resection of the aganglionic intestine.…”
Section: Introduction and General Concepts On The Enteric Nervous Systemmentioning
confidence: 99%
“…Most MEN2A and FMTC mutations affect cysteine residues in the extracellular cysteine-rich domain (exons 10 and 11). A common mutation found in over 80% of typical MEN2A patients is a missense mutation at amino acid 634, particularly C634R, whereas FMTC/MEN2A mutations are spread among the various cysteine molecules of this region [ 58 , 59 ]. Patients with sporadic MTC also harbour somatic RET mutations in around 50% of cases, primarily at codons 768, 804, and 918.…”
Section: Men2 Syndromementioning
confidence: 99%
“…To answer this question, one must consider what previous studies have shown: 1) expression of physiological levels of human Ret with the MEN 2B mutation in mice will not induce tumor formation (MTC, pheochromocytoma, or intestinal ganglioneuromas); 2) expression of physiological levels of murine Ret with the MEN 2B mutation in mice will induce C-cell hyperplasia, pheochromocytomas, and certain ganglioneuromas, but not MTC; 24 and 3) expression of supraphysiological levels of human Ret with the MEN 2B mutation (or the MEN 2A mutation) in mice will induce MTC and other associated tumors. [53][54][55][56][57] It seems possible that intrinsic differences in the human and mouse RET proteins exist such that oncogenic signals from physiological levels of mutant human RET in a mouse are insufficient to drive tumor formation (and that this insufficiency can be overcome by overexpressing mutant human RET). Alternatively, modifier genes may exist that must also be expressed in addition to activated Ret for the development of MTC and that this requirement for modifier genes can be overcome by overexpressing mutant human RET.…”
Section: Discussionmentioning
confidence: 99%